2012
DOI: 10.1080/09500693.2012.728012
|View full text |Cite
|
Sign up to set email alerts
|

From Teaching Physics to Teaching Children: Beginning teachers learning from pupils

Abstract: This paper discusses the development of beginning physics teachers' pedagogical content knowledge (PCK) in the context of teaching basic electricity during a one-year Professional Graduate Diploma in Education course (PGDE) and beyond. This longitudinal study used repeated semi-structured interviews over a period of four-and-a-half years. The interview schedule followed a line of development through the secondary school electrical syllabus in Scotland. Fifteen student teachers were interviewed during the PGDE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…No difference was observed in the PCK of teachers with or without classroom experience. Findlay and Bryce (2012) also reported that secondary science teachers built their pedagogical knowledge while working in classrooms. Their study followed six Scottish physics teachers over their first four and a half years on the job.…”
Section: Studies In Science Educationmentioning
confidence: 94%
“…No difference was observed in the PCK of teachers with or without classroom experience. Findlay and Bryce (2012) also reported that secondary science teachers built their pedagogical knowledge while working in classrooms. Their study followed six Scottish physics teachers over their first four and a half years on the job.…”
Section: Studies In Science Educationmentioning
confidence: 94%